Analisis Unsur Intrinsik Cerita Rakyat Ulumbu dari Manggarai - Juliandro Ferdian Harjoni; Marselus Robot; Margareta P. E. Djokaho (Lembaga Yasin AlSys, 2026)
The Ulumbu folktale from Manggarai is a cultural heritage that contains moral values and local wisdom, but the intrinsic elements that constitute the unity of the story have not been widely examined in specific studies. This study aimed to identify and describe the intrinsic elements of the Ulumbu folktale. This study employed a qualitative descriptive method with a structural approach. The data source was the text of the Ulumbu folktale contained in Mauritius Fardy Jebaru’s undergraduate thesis entitled Analisis Struktur Naratif Teks Cerita Rakyat Ulumbu dalam Perspektif Seymour Chatman. The text was derived from interviews conducted with informants in the previous study and was used as the object of analysis. Data were collected by reading, recording, and classifying excerpts using coding cards and were then analyzed through the stages of identification, classification, description, interpretation, and conclusion drawing. The findings showed that the Ulumbu folktale was constructed through seven intrinsic elements: major and minor themes; a plot comprising five stages; four characters and their characterizations; spatial, temporal, and social settings; a third-person point of view; personification and repetition as figures of speech; and a moral message. This study concludes that these seven elements collectively constitute the structural unity of the story, thereby producing a coherent and meaningful literary work. These findings contribute to an understanding of the structure of Manggarai folktales and support the documentation and preservation of regional literature as part of cultural heritage.